A Commentary Reflection of Moral Psychology Based on Embodied Cognition - Yang, Shaogang (ETHICS IN PROGRESS, 2018)
The rise of embodied cognition in recent ten years has brought about significant influence on the research of moral psychology. On the one hand, the development of neuro-cognitive science has facilitated the research of morality deeply into the mirror neurons of brain, no longer being limited simply on the philosophical speculation; and on the other hand the experimental research of embodied cognition has provided new evidence for some traditional and philosophical moral issues and even made some new recognition of the issues which are different from the traditional interpretations. Tracing back to the research of the Western moral psychology, we find that cognitive rationality and virtual ethics are the two main research lines for moral psychology.（1）J. Piaget and L. Kohlberg opened a way for the research of cognitive development of morality, and their successors have formed new Kohlbergian School, such as the moral judgment theory based on DIT proposed by J. Rest and his colleagues, G. Lind’s dual-aspect theory based on his MCT and KMDD®; the social cognitive domain theory proposed by E. Turiel and his colleagues; the feminine caring ethics advocated by C. Gilligan and N. Noddings; the Social Intuitionist Theory proposed by J. Haidt based on evolutionary psychology, cultural psychology and neuro-cognitive science and so on. (2) The traditional moral philosophy and ethics have opened another way to the research of character education and virtues, such as the American movement of character education facilitated by W, Bennett and T. Lickona and others; the argument between J. Rawls and R. Nozick on moral problems; A. C. MacIntyre’s moral critique to the Western societies and his virtue ethics and so on. Since 21st century the research of embodied cognition has broken through the limitation of the traditional research on moral psychology, attempting to realize the new synthesis of intellect, human body and its environment, and therefore started the embodied research of moral judgment which is unfolded around the three dimensions of physical cleanliness, disgust, body temperature and body movements. I has also assimilated Piaget and Vygotsky’s ideas of psychological development, the theory of conceptual metaphor in cognitive semantics and the theory of evolutionary psychology, and made its theoretical interpretation and exploration for the embodied effect of moral judgment. Since the variable of physical body could have its influence on individual moral judgment by means of one’s emotion and cognitive elements, the moral judgment based on embodied cognition should be integrated with the theories of moral judgment, especially with moral competencies that are the core of moral judgment, and meanwhile the relationship between the embodied cognition and moral intuition should be deeply explored, and the issues such as chronergy, that is, time efficiency, and dynamics taken place when there is the embodied effect should be further examined, the regulated variables of embodied effects while making moral judgment and the individual differences should also be found out through detailed research. And finally we should check out the embodied effects of moral judgment through the cross-cultural comparison.